2020
DOI: 10.1007/s00018-020-03467-1
|View full text |Cite
|
Sign up to set email alerts
|

The Rab5 activator RME-6 is required for amyloid precursor protein endocytosis depending on the YTSI motif

Abstract: Endocytosis of the amyloid precursor protein (APP) is critical for generation of β-amyloid, aggregating in Alzheimer's disease. APP endocytosis depending on the intracellular NPTY motif is well investigated, whereas involvement of the YTSI (also termed BaSS) motif remains controversial. Here, we show that APP lacking the YTSI motif (ΔYTSI) displays reduced localization to early endosomes and decreased internalization rates, similar to APP ΔNPTY. Additionally, we show that the YTSI-binding protein, PAT1a intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 76 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…In contrast, detection with anti-c-myc antibodies demonstrated that higher amounts of APPΔCT were pulled down via trans -coimmunoprecipitation compared with APP WT (Figure 4B) . This demonstrates that indeed, a higher presence of APP at the cell surface due to strongly impaired endocytosis (Eggert et al, 2020) goes along with a higher amount of APP trans -dimers.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, detection with anti-c-myc antibodies demonstrated that higher amounts of APPΔCT were pulled down via trans -coimmunoprecipitation compared with APP WT (Figure 4B) . This demonstrates that indeed, a higher presence of APP at the cell surface due to strongly impaired endocytosis (Eggert et al, 2020) goes along with a higher amount of APP trans -dimers.…”
Section: Resultsmentioning
confidence: 84%
“…It has been reported that APP seems to be almost completely dimerized at the cell surface and involves the presence of heparan sulfate at the plasma membrane (Gralle et al, 2009). Surface localization of APP is a balance from its transport in the secretory path, its internalization and its processing (Eggert et al, 2018a; Eggert et al, 2020; Eggert et al, 2022; Eggert et al, 2018b). For example, reduced proteolysis of APP in processing deficient mutants leads to an increased surface localization of APP, resulting in elevated trans -dimerization and synapse formation (Stahl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amyloid cascade hypothesis suggests that Aβ plaques accumulate in the brain, leading to neurodegeneration and even cell death. The breakdown of APP depends on three different secretases (α‐, β‐, and γ‐) (Eggert et al, 2020). In the nonamyloidosis pathway, full‐length APP is cleaved by α‐ and γ‐secretase to produce nonneurotoxic fragments (Yeung et al, 2019).…”
Section: Alzheimerʼs Disease and Ferroptosismentioning
confidence: 99%
“…(α-, β-, and γ-)(Eggert et al, 2020). In the nonamyloidosis pathway, full-length APP is cleaved by α-and γ-secretase to produce nonneurotoxic fragments(Yeung et al, 2019).…”
mentioning
confidence: 99%